Development of a direct fuel injector for a two-stroke gasoline engine - Mohd Ali, Mas Fawzi (2007)
A prototype pressure-swirl injector was designed to suit an arbitrary twostroke, gasoline direct injection engine requirement. A commercial computational fluid dynamics software FLUENT was used as a tool to analyze the performance of the conceptual design. A prototype injector was fabricated once the conceptual design met the requirements. The fabricated prototype injector was then subjected to a series of specification tests such as leak test, static flow rate test and discharge coefficient test. A dedicated test rig was set up to evaluate the performance of the prototype injector. The spray images at specified time frame were illuminated by Nd:Y AG laser sheet and captured using a high-speed digital camera. The stored images were analyzed to give data of spray angle, and droplet Sauter mean diameter at fuel-air pressure differential ranging from 1.0 to 5.0 MPa, with a step size of 1.0 MPa. From the tests, the prototype injector static flow rate, half spray cone angle and the droplet Sauter mean diameter at fuel injection pressure of 5.0 MPa was found to comply with the outlined requirements, which are approximately 475 cc/min, 32° and 19 11m respectively. Finally, the experimental data was compared with the calculated data. It was found that the measured data of static flow rate, discharge coefficient, and droplet Sauter mean diameter were higher than the computed data at fuel-air pressure differential between 1.0 and 3.0 MPa. In contrast, the calculated initial spray angle was overestimated by 3% at all tested fuel-air pressure differentials.